Inhibition of Tubulin β-chain May Play a Regulatory Role in the Development of Rheumatoid Arthritis - Zhao, Yan; Li, Shufeng; Jihong, Pan; Zhang, Rui; Li, Zhiyuan; Meng, Qingsong (Aktuelle Rheumatologie, 2019)
Pathological characteristics of Rheumatoid arthritis (RA), a systemic autoimmune disease, includes abnormal proliferation of synovial fibroblasts and increased angiogenesis.The study assessed the effect of tubulin β-chain gene (TBB) gene knockdown on the behaviour of rheumatoid arthritis (RA) fibroblast-like synoviocytes (SFs), which is significantly affected by the synthesis of tubulin. Cultured SFs were isolated from the mixed knee-joint synovial tissue of five RA patients and treated with siRNA targeting TBB. Knockdown efficiency and expression of relevant genes were detected by RT-PCR following 24 h and 36 h of transfection. MTT, Transwell, and wound scratch assays and flow cytometric analysis were used to assess cell proliferation and invasive and migratory capacity following TBB knockdown. The expression of TBB was detected after inhibition of the ERK, STAT3 and NF-kB pathways. The expression of IL-17, TNF-α, IL-1α, IL1-β, and IL-6 was quantified following TBB knockdown. The proliferation, invasion, and migration of RASFs were significantly decreased following TBB knockdown. ELISA showed a significant decrease in interleukin 1β (IL-1β) secretion and insignificantly reduced secretion of TNF-α, IL-17, and IL-1α after TBB knockdown. The expression of TBB in RASFs decreased with the increasing concentration of a STAT3 pathway inhibitor while TBB expression increased after down regulation of the ERK pathway. These results support a protective role for TBB knockdown in suppressing RASFs, laying a foundation for further studies on the pathogenic mechanisms of RA.
Keywords: tubulin β-chain; siRNA; rheumatoid arthritis; fibroblast-like synoviocytes